2018
DOI: 10.1063/1.5019770
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mechanosensitive channel MscL expression in cancer cells on 3D confined migration

Abstract: Metastatic cancer cells migrate through constricted spaces and experience significant compressive stress, but mechanisms enabling migration in confined geometries remain unclear. Cancer cell migration within confined 3-dimensional (3D) microfluidic channels has been shown to be distinct from 2D cell migration. However, whether 3D confined migration can be manipulated by mechanosensory components has not been examined in detail. In this work, we exogenously introduced a mechanosensitive channel of large conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Cells might “decide” to migrate singly through constrictions, even going so far as to rupture their nuclei 28,29 . Heureaux-Torres and coworkers 12 presented data in this issue, suggesting that signaling from the mechanosensitive channel of large conductance (MscL) may serve as a “go”-“no go” switch; MscL expressing cancer cells migrated at the same velocity as their non-expressing counterparts, but Heureaux-Torres observed that MscL cells more frequently get “stuck” at the entrance of constricting channels. They fail to crawl into a channel at higher rates, perhaps sensing that the constriction is too excessive.…”
Section: I've Got a Feelin': Sensing And Response In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Cells might “decide” to migrate singly through constrictions, even going so far as to rupture their nuclei 28,29 . Heureaux-Torres and coworkers 12 presented data in this issue, suggesting that signaling from the mechanosensitive channel of large conductance (MscL) may serve as a “go”-“no go” switch; MscL expressing cancer cells migrated at the same velocity as their non-expressing counterparts, but Heureaux-Torres observed that MscL cells more frequently get “stuck” at the entrance of constricting channels. They fail to crawl into a channel at higher rates, perhaps sensing that the constriction is too excessive.…”
Section: I've Got a Feelin': Sensing And Response In Cancermentioning
confidence: 99%
“…They deepen understanding by advanced imaging or by building simple systems to focus on a microenvironment property, such as ECM that is stiffer, 1 more dense, 2 crosslinked, 3 aligned, 1 or less porous 3 . The efforts profiled here investigate or summarize our knowledge of tumors in four ways: (1) some clarify how intratumor or stromal fluid 4,5 or blood flow 6 drives tumor behavior, (2) others develop model in vitro systems to understand 7–10 or measure 11 tumor behavior, (3) still others examine how cancer cells sense changes in their niche 12 and how that drive behaviors, 13,14 and (4) a few are more integrative with computational simulations of complex processes in cancer 15–17 …”
Section: Introductionmentioning
confidence: 99%
“…MscL can be used for improving the absorption of membrane-impermeable drugs and bioactive materials into cells via ultrasonic [15] or chemical [14] activation processes. The introduction of bacterial MscL in mice has shown a reduced metastasis in the lungs [16] . Furthermore, engineered MscL expressed in rat hippocampal neurons is activated by a low-pressure ultrasound pulse, which controls neuronal excitation [15] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells also experience compressive stress when they migrate through capillary and confined tissue microenvironment [6][7][8][9] . Reports have shown that compressive stress alters cell-cell attachment, cell adhesion, traction force, proliferation, differentiation, and migration 2,4,10,11 . Recent in vivo studies show that compressive stress stimulates tumorigenic signaling by increasing β-catenin signaling in colon epithelial cells 12 , and strategies to release compressive stress can indeed enhance the efficiency of anti-tumor treatment 13 .…”
Section: Introductionmentioning
confidence: 99%